2005
DOI: 10.1681/asn.2005050487
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism in Renal Transplant Recipients

Abstract: Cyclosporine A (CsA) and tacrolimus have been associated with an increased risk for diabetes after transplantation, whereas sirolimus is deemed to be devoid of any effect on glucose metabolism. This study was performed to investigate the effect of the withdrawal of calcineurin inhibitors and the switch to sirolimus on peripheral insulin resistance and pancreatic ␤ cell response. Twenty-six patients who received a kidney transplant and discontinued CsA and were converted to sirolimus and 15 recipients of subopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
2
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(170 citation statements)
references
References 49 publications
9
152
2
7
Order By: Relevance
“…In accordance with an impairment of insulin signaling, insulin-stimulated glucose uptake was reduced in human adipocytes treated for a short-term (15 min) or long-term treatment (20 h) with rapamycin at therapeutic concentrations (72). At the whole body level, the switch of calcineurin inhibitors to sirolimus induces a worsening of insulin resistance associated with a deterioration of compensatory insulin secretion, leading to new-onset diabetes (63). Interestingly, Kulke et al (72) first reported in 2009 that the use of everolimus in four patients with insulinoma and refractory hypoglycemia was associated with improved glycemic control.…”
Section: Effects Of Mtor Inhibitors On Lipids "mentioning
confidence: 99%
“…In accordance with an impairment of insulin signaling, insulin-stimulated glucose uptake was reduced in human adipocytes treated for a short-term (15 min) or long-term treatment (20 h) with rapamycin at therapeutic concentrations (72). At the whole body level, the switch of calcineurin inhibitors to sirolimus induces a worsening of insulin resistance associated with a deterioration of compensatory insulin secretion, leading to new-onset diabetes (63). Interestingly, Kulke et al (72) first reported in 2009 that the use of everolimus in four patients with insulinoma and refractory hypoglycemia was associated with improved glycemic control.…”
Section: Effects Of Mtor Inhibitors On Lipids "mentioning
confidence: 99%
“…However, it is important to note that in vivo studies designed to reveal the importance of mTORC1 using rapamycin are less than ideal because of modulation of insulin sensitivity. 63,64 In addition, it is now accepted that a major limitation of rapamycin for in vivo and in vitro studies is the inhibition of mTORC1 activity toward only a subset of mTORC1 substrates. 8,9,[65][66][67] Therefore, inhibiting mTORC1 signaling in vivo by genetic deletion of Raptor in β cells will provide new insights into the role of this pathway in nutrient-and growth factor-dependent regulation of β-cell proliferation.…”
Section: How Downstream Mtorc1mentioning
confidence: 99%
“…Chronic administration of rapamycin has been associated with higher incidence of diabetes, although the relative contribution of β-cell dysfunction and insulin resistance to this effect is difficult to dissect. 63,64 It is possible that the alterations in insulin sensitivity could result from the signals from growth factors and nutrients, 69,[100][101][102][103][104][105] induces controlled growth and is rarely associated with malignancy. 106,107 The current evidence supports the concept that mTORC1 is active in states of increased insulin demand and plays a major role in β-cell expansion and proliferation induced by AKT and insulin resistance.…”
Section: How Decreased Akt Signaling By Mtorc1-mediated Negativementioning
confidence: 99%
“…Sirolimus is also independently associated with new-onset diabetes in kidney transplant recipients (35). Conversion from a target of rapamycin inhibitor to another immunosuppressive agent is a common practice, largely because of the adverse effects of this class of agents, including intractable hyperlipidemia.…”
Section: Role Of Immunosuppressionmentioning
confidence: 99%